Fabrication of PHFPO Surface‐Modified Conductive AgNWs/PNAGA Hydrogels with Enhanced Water Retention Capacity toward Highly Sensitive Strain Sensors - He, Yuan‐Yuan; Wang, Cong; Song, Xue; Zhang, Lansheng; Chang, Long; Yuan, Chentai; Hu, Huan; Liu, Chun‐Hua; Zhu, Yuan‐Yuan (Macromolecular rapid communications., 2024)
Conductive hydrogels, characterized by their unique features of flexibility, biocompatibility, electrical conductivity, and responsiveness to environmental stimuli, have emerged as promising materials for sensitive strain sensors. In this study, a facile strategy to prepare highly conductive hydrogels is reported. Through rational structural and synthetic design, silver nanowires (AgNWs) are incorporated into poly(N‐acryloyl glycinamide) (PNAGA) hydrogels, achieving high electrical conductivity (up to 0.88 S m−1), significantly enhanced mechanical properties, and elevated deformative sensitivity. Furthermore, surface modification with polyhexafluoropropylene oxide (PHFPO) has substantially improved the water retention capacity and dressing comfort of this hydrogel material. Based on the above merits, these hydrogels are employed to fabricate highly sensitive wearable strain sensors which can detect and interpret subtle hand and finger movements and enable precise control of machine interfaces. The AgNWs/PNAGA based strain sensors can effectively sense finger motion, enabling the control of robotic fingers to replicate the human hand's gestures. In addition, the high deformative sensitivity and elevated water retention performance of the hydrogels makes them suitable for flow sensing. These conceptual applications demonstrate the potential of this conductive hydrogel in high‐performance strain sensors in the future. The study presents a straightforward strategy for integrating silver nanowires into poly(N‐acryloyl glycinamide) (PNAGA) hydrogels, resulting in high electrical conductivity, significantly enhanced mechanical properties, and elevated sensitivity to deformation. Surface modification with polyhexafluoropropylene oxide markly improves the water retention capacity and comfort of this hydrogel material. These hydrogels are utilized to fabricate highly sensitive strain sensors for applications in human–machine interfaces and flow sensing.